Impact of Accounting Information System on Organizational Performance of Government Institutions (International Forum of Researchers and Lecturers, 2024)
AIS has become an indispensable tool for government institutions to fulfill their objectives and enhance overall performance. This study was conducted to assess the impact of AIS on the organizational performance of government institutions in Iba, Zambales, participated in by the 50 government offices in the municipality. The findings indicates that there is a perceived strong agreement on the utilization of AIS in terms of accuracy, enhancing quality function, user satisfaction, and informed decision-making; and also strong agreement on the effectiveness and efficiency of using AIS in government organizations’ performance; there is a significant difference in terms of accuracy on the utilized AIS based on sex, highest educational attainment, government office, and years working with AIS; in terms of enhancing quality function based on sex, government office, and years working with AIS; in terms of user satisfaction based on government office and job title; in terms of informed decision-making based on sex; in terms of effectiveness and efficiency in using AIS based on government offices; and there is a significant relationship between the utilized AIS and organizational performance.